PENDAFTARAN PASIEN RAWAT INAP DI REKAM MEDIS ELEKTRONIK RUMAH SAKIT TK III BHAYANGKARA BANJARMASIN - Ansari, Muhammad Rashif; Noviani, Nurul (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2024)
The implementation of electronic medical records improves the efficiency of medical record management. It facilitates information access and data integration between systems, thereby reducing human error. This study aims to determine how to register inpatients in the electronic medical records of the Bhayangkara Banjarmasin Class III Hospital. The method used is descriptive qualitative research, with data collection through observation and interviews. The subjects of this study consisted of 3 people: Head of the Medical Records Unit, Head of the IT Unit, and Inpatient Registration Officer. The results of the study indicate that inpatient registration in terms of human resources has undergone training and understands electronic medical records. Inpatient registration is in accordance with the SOP, but there are still errors in the network and SIMRS Khanza during service hours